International political economy and future of multilateralism: a platform for cooperation for G20 sovereign wealth funds - Flynn, Curran (My University, 2020)
This policy brief proposes the creation of a platform for cooperation among the Group of Twenty (G20) states' sovereign wealth funds (SWFs). The platform should allow for multiple practices that include long-term cooperation, direct investments, and the formation of bilateral/trilateral/multilateral investment accords. Ultimately, it would encourage the G20 states to strengthen their economic cooperation, bolster mutual interests, improve multilateralism, and develop opportunities for their SWFs. Addi- tionally, it would act as an emergency tool in easing the impact of a global crisis, such as the current COVID-19 pandemic, as it can be employed as an anti-crisis measure via the investments of the G20 states’ SWFs.
Task Force 5: The future of multilateralism and global governance
Keywords: International Development; International Integration; Economic policy making; International Institutions; International Political Economy; International economics, finance, trade and development; Public Planning/Policy; Sovereign Wealth Funds